Online English Learning during Covid-19 Pandemic - Sartipa, Dewi (Jurnal Humaniora dan Ilmu Pendidikan, 2021)
Purpose: This article aims to describe English learning in the Covid-19 Pandemic Era. This article also explains the importance of the Internet in the learning process and the importance of parents in the development of students in the Covid-19 Pandemic Era. Research methodology: This study used a descriptive method. Results: This study suggests that parents should motivate their children in this situation because the learning process is carried out at home, and only parents can directly monitor the learning process. Limitations: This study has limitations. It is the information of parents who guide their students in the learning process, especially English Subject in the Covid-19 pandemic. Contribution: The study is beneficial for teachers and parents to conduct a better learning strategy during Covid -19 pandemic.